Grooves on the cortex of the Epigravettian lithic industry in the broader context - Nerudová, Zdeňka; Lepcio, Petr (Hugo Obermaier-Society for Quaternary Research and Archaeology of the Stone Age, 2024)
The southern part of the Brno urban agglomeration (Czech Republic) is a crucial region for understanding the Late Upper Palaeolithic (Epigravettian) occupation in Central Europe. Despite limited archaeological research in the urban area, the newly uncovered Brno-Štýřice IIIb site has provided additional information about the character of the Palaeolithic occupation, the hunted fauna, and climate. Our information about the Late Palaeolithic has been increased by recent finds. In this article we present two unique finds, both lithic chipped pieces with grooves on the cortex, found in a well-dated stratigraphic context at the recently excavated area. The different kinds of grooves on the cortex of the chipped stone artefacts can be understood as an example of possible intentional modification of the subjects. We will try to resolve the question of whether these pieces can be understood as non-utilitarian pieces, decorations, symbols (which are rare in the Epigravettian), or if the pieces represent the results of everyday Palaeolithic life.

The southern part of the Brno urban agglomeration (Czech Republic) is a crucial region for understanding the Late Upper Palaeolithic (Epigravettian) occupation in Central Europe. Despite limited archaeological research in the urban area, the newly uncovered Brno-Štýřice IIIb site has provided additional information about the character of the Palaeolithic occupation, the hunted fauna, and climate. Our information about the Late Palaeolithic has been increased by recent finds. In this article we present two unique finds, both lithic chipped pieces with grooves on the cortex, found in a well-dated stratigraphic context at the recently excavated area. The different kinds of grooves on the cortex of the chipped stone artefacts can be understood as an example of possible intentional modification of the subjects. We will try to resolve the question of whether these pieces can be understood as non-utilitarian pieces, decorations, symbols (which are rare in the Epigravettian), or if the pieces represent the results of everyday Palaeolithic life.
Grooves on the cortex of the Epigravettian lithic industry in the broader context
Keywords: analyses; Czech Republic; Epigravettian; grooves on the cortex; analyses; Czech Republic; Epigravettian; grooves on the cortex